EFEKTIFITAS SISTEM PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN TERHADAP TUJUAN PEMIDANAAN - Sri Wulandari (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
Correctional system is a series of law enforcement that aims to make prisoners aware of his mistake, realize yourself and do not repeat his mistakes and be accepted back in society and play an active role in development, more equitable as good citizens and responsible. The imposition of imprisonment for the convicted person's right to freedom means the seized of concerning human dignity. Therefore for achieving the goals of sentencing, motivation and characteristics of correctional officers and the community were necessary in a sustainable and integrated either at the time prisoners in the Penitentiary (intra-mural) or outside Correctional Institution (extra mural). The lack of attention Prison officers and community participation inmates in the prison system of criminal justice may be possible kriminogen and become ineffective.